Financial Sustainability of Small Business Entities: Features and Principles of Preservation in Crisis Conditions - Shushkova Yuliia V.; Fatsiievych Roman Ya. (Bìznes Inform, 2023)
The article emphasizes the relevance of the formation and implementation of public policy for the development of the small business sector in the conditions of wartime, in particular in the aspect of minimizing the negative impact of existing financial threats to the sustainable functioning of its representatives. The aim of the study is to identify the features and determine the principles of the State policy of maintaining the financial stability of the small business sector in a crisis. The novel problems of guaranteeing the financial stability of small businesses in Ukraine in the conditions of wartime are identified. The essential and semantic characteristics of the concept of «financial sustainability» at the level of the small business sector have been developed. It is asserted and then proved that this is the very state of development of the financial and credit system and the economic environment of entrepreneurial activity, in which the financial threats of deterioration of the financial and economic condition of a critical mass of small businesses are minimized. On this basis, the leading objects of the State policy are: fair competition; absence of the transaction and transformation costs; availability of external investments and loans; acceptable cost of raising and using capital; development of financial and credit infrastructure; an effective system of financial risk insurance. The features of management of financial sustainability of entities of the small business sector are determined by such management functions as analysis, planning and regulation of the financial condition, organization, motivation, and control. The main challenges and threats to the financial stability of Ukrainian business in the conditions of wartime are identified. An instrumentarium for countering the challenges and threats of financial destabilization of the subjects of the small business sector of Ukraine has been elaborated and substantiated, which should be implemented in the following areas: application of progressive methods of anti-crisis financial management; supplementing traditional approaches with progressive levers and mechanisms of financial management; introduction of effective additional financial instruments; development of institutional and legal support for the processes of strengthening financial sustainability; modernization of information and analytical support of financial management in the field of monitoring and development and implementation of policies to guarantee the appropriate level of financial sustainability of business.